The Effects of Teaching Model and Learning Style Towards Students’ Speaking Skill At Private Schools In Rangkasbitung - Erna Irawati (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2015)
This experimental study aims to identify how significant the effect of collaborative MURDER teaching model towards students’ speaking skill, the effect of learning style towards students’ speaking skill and the interaction effect of teaching model and learning style towards students’ speaking skill. The population is students of Al-Qudwah and Al-Bayan Integrated Junior High School, and the sample are students in class VIII grade consist of thirty and thirty one students in which their English ability are almost same. The technique of getting the samples in this research is clustersampling to get sample randomly. Data is got by using test, posttest after treatment. This research uses oral test to measure students’ speaking skill. The result of this research are: (1) there is significant effect of collaborative MURDER teaching model towards students’ speaking skill. (2) There is significant effect of learning style towards students’ speaking skill. (3) There is no interactive effect of teaching model and learning style towards students’ speaking skill. The effect of teaching model towards students’ speaking skill that has been taught by collaborative MURDER teaching model is better than students’ speaking skill that has been taught without collaborative MURDER teaching model. In learning style, students in visual learning style are better than students in auditory learning style. CollaborativeMURDERcanbe an alternativelearning modelthatcanbe usedinJunior High School.